2014
DOI: 10.1016/j.eats.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction With Preservation of Femoral Anterior Cruciate Ligament Stump

Abstract: Anterior cruciate ligament (ACL) reconstruction with preservation of either the remnant or the tibial stump is performed with the hope of improving the vascularization and proprioceptive function of the graft. Remnant preservation is technically difficult because it hinders the visualization of the intra-articular tunnel site. Taking a cue from the concept of tibial stump preservation, we have modified our ACL reconstruction technique to preserve a sleeve of the soft tissue and ACL stump attached to the femora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A short remnant has been reported in the majority of cases after careful notchplasty. In the present study, we tought it may be beneficial to preserve the ACL remnant at the femoral insertion area, as in the similar technique in which the tibial remnant is preserved (20). In Group A, ACL remnants and/or footprints were not detected at the femoral attachment site in 6 patients (92,86%).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A short remnant has been reported in the majority of cases after careful notchplasty. In the present study, we tought it may be beneficial to preserve the ACL remnant at the femoral insertion area, as in the similar technique in which the tibial remnant is preserved (20). In Group A, ACL remnants and/or footprints were not detected at the femoral attachment site in 6 patients (92,86%).…”
Section: Discussionmentioning
confidence: 84%
“…The clinical results of remnant-conserving surgery are still controversial altough the results of histomorphological and animal studies. There are some studies report the positive effect of the preservation of the tibial stump or remnant (19)(20)(21) while other studies report that remnant-preserving has no effect (22) or effective only on knee instability (23). The lack of standardization in study designs and short follow-up periods are the limitations of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although removal of any remaining ACL assists in locating the intra-articular bone tunnel and improves the accuracy of surgical procedure, histological studies have confirmed that an abundant blood supply and proprioceptors are present in ligaments and the synovium [ 15 ]. In the present study, all patients underwent reconstruction with remnant preservation [ 16 ]. The remnant ACL was as far as possible pulled into the bone tunnel or tunnel portal when the graft was installed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely published that the revascularization of the tendon graft after ACL reconstruction by surgery is a crucial step in the "ligamentization" process (Arnoczky, Tarvin, & Marshall, 1982;Butler et al, 1989;Petersen et al, 2003;Yoshikawa et al, 2006). In fact, some techniques have been described trying to enhance both the revascularization and the proprioception after ACL reconstruction preserving the tibial and/or femoral stumps, which can benefit the patient (Lee, Kwon, Kim, Choi, & Min, 2008;Song et al, 2013;Nag & Gupta, 2014). Revascularization is one of the first processes that must occur for a successful integration of the tendon after ACL reconstruction (Tohyama, Yoshikawa, Ju, & Yasuda, 2009).…”
Section: Discussionmentioning
confidence: 99%